GAMBARAN KESEJAHTERAAN PSIKOLOGIS MANTAN TENAGA KERJA WANITA - Rakasi, Derry; Hakim, Lukmanul; Hartono, Roni (JURNAL PSIMAWA, 2019)
This study aims to determine the description of psychological well-being of former female workers who received objectionable acts during the migration process or upon returning home. This study is a qualitative research with descriptive approach. The subjects of this study amounted to three women who domiciled at Sebasang Village Sumbawa Regency that has professional background as former female workers. The data analysis shows that two subjects (AA and N) have good psychological well-being because they have been able to fulfill all aspects of self accepance, positive relations with others, autonomy, environmental mastery, purpose of life and personal growth. Meanwhile, NZ showed the opposite result. The difficulties to fulfill her psychological well-being caused by low acceptance towards her experiences and past who had worked as a former migrant worker which ultimately gives effect to her perception of defining meaningful life.